†Estelestes ensis (Mammalia, Metatheria) from the early Eocene of Baja California (Mexico) as a generalized polydolopimorphian. (March 2023) - Goin, Francisco J.; Vieytes, Emma Carolina; Crespo, Vicente D.; Oliveira, Édison V.
Abstract : Estelestes ensis Novaceck et al., 1991 is a curious Paleogene metatherian mammal recognized on the basis of a single specimen from Baja California (Mexico) in southern North America. It comes from early Eocene (Wasatchian age) levels of the Las Tetas de Cabra Formation at "Marsupial Hill" in the Lomas Las Tetas de Cabra site (also known as Punta Prieta; see Novaceck et al., 1991 ). The specimen consists of a fragmentary left mandible with the last premolar, the roots of the first two molars, and almost complete last two molars (Fig. 1). It was referred to the Didelphini (Marsupialia, Didelphimorphia, Didelphidae, Didelphinae) even though Novaceck et al. (1991 ) stated that the overall morphology of the type specimen poses intriguing problems regarding its relationships. For example, the very deep, robust jaw of Estelestes distinguishes it from any other Holarctic "didelphine" (at the time Novaceck et al., 1991 published their work, both the concept and extent of Didelphidae and Didelphinae were much broader than today). Interestingly, they concluded that Estelestes had close affinities with " Mirandotherium " (lapsus calami for Mirandatherium ), from the early Eocene of Itaboraí, in southeastern Brazil. "Resemblance between the two taxa is nevertheless striking, once again raising the possibility of close relationships among certain early members of the Northern Hemisphere and South American Didelphinae" (Novaceck et al., 1991, p. 16). The affinities of Mirandatherium are contested, having been regarded as part of the Didelphimorphia (e.g., de Paula Couto, 1952a ) or Microbiotheria (e.g., Marshall, 1987 ; McKenna and Bell, 1997 ; Oliveira and Goin, 2011 ), or even as an alphadontian (Carneiro, 2019 ).